Empowerment Program for Tailor Women In Glagaharum Village Through Segmentation, Targeting And Positioning Education: Program Pemberdayaan Ibu-Ibu Penjahit Desa Glagaharum Melalui Edukasi Segmentasi, Targeting dan Positioning - Avizenna, Neola Omar; Satyanegara, Teresa Samantha; Setiawan, Angie Ivana; Br Sitepu, Sri Nathasya (Universitas Lancang Kuning, 2024)
The residents of Glaagaharum Village have limitations to meet household needs. The income of each head of a family has not been able to meet the living needs of every household. This causes housewives to take on an additional role as a financial support. Housewives who have skills begin to receive garment sewing. Tailor women need to increase their capacity so that they can increase their income. Capacity building through the empowerment program of Glagaharum Village tailors through segmentation, targeting and positioning education. This program was attended by 13 women tailors in Glaagaharum Village. The implementation of the program lasted for 6 months at the Glaagaharum Village Hall. The empowerment program uses the in-house training method. The training was held with an interactive system (pre-test, discussion, simulation, material provision, posttest). The objectives of the empowerment program can be grouped into three parts, namely: 1) providing knowledge related to market segmentation, 2) helping tailors determine targets/targets for product sales, 3) increasing knowledge while setting (positioning) product position in the market. The results of the empowerment program of Glagaharum Village tailors include: 1) market segmentation in the big market (sales with a wholesale system), 2) sales targets targeting Muslim men's and women's clothing with typical Glaagaharum Village motifs, 3) Muslim clothing products made by Glaagaharum Village tailors to become pioneers/pioneers of Muslim clothing in the big market.